Estímulos com significado pré-experimental no estabelecimento de classes de equivalência - Marin, Ramon (2020)
This study aimed to investigate whether after establishing three-member equivalence classes with abstract stimuli (ABC) and teaching relations between one meaningful stimulus and one member of equivalence class (DA), stimuli D would become part of the previous equivalence class (ABCD). It was also evaluated the merger of classes by testing the emergence of untrained relations between abstract stimuli (B and C) and images that carries a similar meaning to D stimulus in everyday life (E, F, G, H, I, J, K, L, and M). College students participated in three experiments (n = 21, 10, and 10). All experiments started with the training of baseline relations (AB and AC) through a matching-to-sample procedure, followed by class formation tests (BC and CB). After the initial tests, the DA relations were trained (D1-A1, D2-A2, and D3-A3). In Experiments 1 and 3, the stimuli of Set D were the written words DENTIST, BAKER, and TABILU; in Experiment 2, the meaningful stimuli were the words DENTIST, BAKER, and MECHANIC. Following the DA training, it was tested the expansion (DB and DC) and the merger of classes (BE, BF, BG, BH, BI, BJ, BK, BL, BM, CE, CF, CG, CH, CI, CJ, CK, CL, and CM). Derivation of untrained relations was observed for most participants in the three studies, resulting in 1) the establishment of the classes ABC (A1B1C1, A2B2C2, and A3B3C3); the expansion of classes, including D stimuli (A1B1C1D1, A2B2C2D2, and A3B3C3D3); and 3) the merger of classes, including the nine novel images (ABCDEFGHIJKLM). Study 3 additionally assessed the possibility of responding by exclusion during the tests. Stimuli E3 to M3 (mechanic related images) were introduced during the tests of the merger of the classes, appearing as models or comparisons depending on each trial. Participants selected these images when the model was TABILU (by the rejection of the images related to the words DENTIST and BAKER) and vice versa, changing the function of the pseudoword, which "acquire the meaning" of the images. These results extended, for the expansion and merger of equivalence classes, the findings supporting the effects of meaningful stimuli on symbolic processes.